2022
DOI: 10.3390/su141912714
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Tamaulipas MSMEs after COVID-19: Intention to Adopt Inbound Marketing Tools

Abstract: Since the emergence of COVID-19, the interruption of non-core activities negatively affected the entire world economy so that companies in emerging countries had to adapt to the “new reality” by seeking new business alternatives. The objective of this study is to determine the intention of Tamaulipas MSMEs to adopt inbound marketing tools based on the Technology Acceptance Model (TAM), considering the variables of attitudes, trust, and perceived technological risk. The proposed model was analyzed using the Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
3
1
Order By: Relevance
“…The tendency to listen to or see other people's comments to find out about a product or service had no impact on a person's interest in purchasing green products. This finding contradicts the previous research, which demonstrated that electronic WOM has a significant effect on purchase intention [50,51]. Respondents in this study are suspected of assuming that reviews obtained from other consumers are not a significant factor in encouraging interest in purchasing green products.…”
Section: The Effect Of Word Of Mouth On Intention To Purchase Green P...contrasting
confidence: 99%
“…The tendency to listen to or see other people's comments to find out about a product or service had no impact on a person's interest in purchasing green products. This finding contradicts the previous research, which demonstrated that electronic WOM has a significant effect on purchase intention [50,51]. Respondents in this study are suspected of assuming that reviews obtained from other consumers are not a significant factor in encouraging interest in purchasing green products.…”
Section: The Effect Of Word Of Mouth On Intention To Purchase Green P...contrasting
confidence: 99%
“…Accomplishing the law and preserving individual rights regarding intimacy is prioritised insofar as it falls under the liberty of navigating on the internet, and, undoubtedly, inbound marketing signifies being non-intrusive [15], is relevant to permission marketing [7], and puts emphasis on ushering in the user's discretion [19]. Therefore, the authors claim that, as far as inbound marketing is concerned, cybersecurity and confidentiality play a crucial role in enhancing best practises [7,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, using inbound marketing will provide greater trust. Simply put, security relies on technology [20]. On this basis, the following hypotheses are put forward:…”
Section: Literature Reviewmentioning
confidence: 99%
“…With more time and less cost, micro-enterprise developments have the potential to increase their quality. We can no longer think about building awareness in microenterprises, but we must start developing the future sustainability of the microenterprises (Müller-Pérez et al, 2022). What cannot be separated from this effort is exploring trends that large corporations welcome in 2023.…”
Section: Introductionmentioning
confidence: 99%